Type I IFN signaling triggers immunopathology in tuberculosis‐susceptible mice by modulating lung phagocyte dynamics. Issue 8 (24th June 2014) - Dorhoi, Anca; Yeremeev, Vladimir; Nouailles, Geraldine; Weiner, January; Jörg, Sabine; Heinemann, Ellen; Oberbeck‐Müller, Dagmar; Knaul, Julia K.; Vogelzang, Alexis; Reece, Stephen T.; Hahnke, Karin; Mollenkopf, Hans‐Joachim; et al.
<x xml:space="preserve">Abstract</x> General interest in the biological functions of IFN type I in Mycobacterium tuberculosis (Mtb) infection increased after the recent identification of a distinct IFN gene expression signature in tuberculosis (TB) patients. Here, we demonstrate that TB‐susceptible mice lacking the receptor for IFN I (IFNAR1) were protected from death upon aerogenic infection with Mtb. Using this experimental model to mimic primary progressive pulmonary TB, we dissected the immune processes affected by IFN I. IFNAR1 signaling did not affect T‐cell responses, but markedly altered migration of inflammatory monocytes and neutrophils to the lung. This process was orchestrated by IFNAR1 expressed on both immune and tissue‐resident radioresistant cells. IFNAR1‐driven TB susceptibility was initiated by augmented Mtb replication and in situ death events, along with CXCL5/CXCL1‐driven accumulation of neutrophils in alveoli, followed by the discrete compartmentalization of Mtb in lung phagocytes. Early depletion of neutrophils rescued TB‐susceptible mice to levels observed in mice lacking IFNAR1. We conclude that IFN I alters early innate events at the site of Mtb invasion leading to fatal immunopathology. These data furnish a mechanistic explanation for the detrimental role of IFN I in pulmonary TB and form a basis for understanding the complex roles of IFN I in chronic inflammation.